AVALIAÇÃO DA VARIABILIDADE DE VARIÁVEIS DE INTERESSE ZOOTÉCNICO PARA COMPARAÇÃO DE MÉDIAS DE TRATAMENTOS APLICADOS A BOVINOS DE CORTE CONFINADOS - SIMIONI, Tiago Adriano; TEIXEIRA, Ubiara Henrique Gomes; PINA, Douglas dos Santos (Brazilian Journal of Biometrics, 2018)
The objective of this study was to evaluate the variability of zootechnical variables of interest for comparison of treatment averages applied to confined beef cattle. The selected variables were: average daily gain, feed conversion, carcass yield, loin eye area, fat thickness, nutrient intake and digestibility. The instability intervals for the coefficients of variation of the variables described above were constructed based on the median (Md) and the pseudo-sigma (PS) of the variable coefficients, considering four ranges of instability: low, medium, high and very high. In this way, the coefficient of variation of performance, consumption and digestibility characteristics were classified as follows: low instability (CV <Md - 1PS), mean instability (Md - 1PS ≤ CV <Md + 1PS) 1PS ≤ CV> Md + 2 PS) and very high instability (CV ≥ Md + 2PS). Thus, the determination of the intervals for the coefficients of variation of the zootechnical variables of interest commonly measured in experiments become extremely important to allow both the selection and the correct application of the several tests of comparison of available averages.